1977
DOI: 10.1073/pnas.74.10.4702
|View full text |Cite
|
Sign up to set email alerts
|

Mysterious form of referred sensation in man.

Abstract: A phenomenon is described in which scratching a small excrescence on the skin on one part of the body is referred to a distant point as a "prick" or a "tingle." "Referral" points are elicited mainly by absent-minded scratching of the skin when attention is not focused on the local sensation produced by the scratch. Location of "referral" points seems to follow definite patterns: in all instances, "referral" points occurred on the same side of the body as the "stimulus" points; each "referral" point was rostral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 5 publications
0
8
1
Order By: Relevance
“…Although there are anecdotal reports of referred sensations in healthy individuals, 33 none of the experimental studies we identified found evidence of referred sensations in the control groups 4,10,13 or in pain-free controls. 5,10 Most studies, including our own, have used modest sample sizes and it may be that the failure of other researchers to identify referred sensations in control groups reflects the difficulty of identifying uncommon phenomena in small populations.…”
Section: Discussioncontrasting
confidence: 59%
“…Although there are anecdotal reports of referred sensations in healthy individuals, 33 none of the experimental studies we identified found evidence of referred sensations in the control groups 4,10,13 or in pain-free controls. 5,10 Most studies, including our own, have used modest sample sizes and it may be that the failure of other researchers to identify referred sensations in control groups reflects the difficulty of identifying uncommon phenomena in small populations.…”
Section: Discussioncontrasting
confidence: 59%
“…Furthermore, in patients with phantom pain after arm amputation diesthetic mislocalizations of somatosensory stimuli from various body parts into the painful phantom limb have been described [15]. Astonishingly, such referred sensations could also appear in apparently healthy subjects [29], although we could not find this in our control group. For example, when acute pain is applied to the hand followed by tactile stimulation of the ipsilateral lip, one may experience an additional phantom-like sensation in the formerly stimulated hand or other body parts, which occurs simultaneously to the lip stimulation [16].…”
Section: Discussionmentioning
confidence: 85%
“…One speculation to account for this observation is that subtle muscle‐induced contractions of the hand in response to toe stimulation (a compensatory response preparatory to breaking the fall in the “stumble” response: [23]) activates the hand representation area in the sensory cortex, although no obvious hand movement was observed. Another possibility is that the response is among the class of atypical forms of referred sensation (e.g., [24]).…”
Section: Discussionmentioning
confidence: 99%